Exploring the multifaceted roles of English for specific purposes practitioners within the transformative paradigm in higher education - Chaovanapricha, Traithana; Champakaew, Wilawan (Asian Journal of Education and Training, 2024)
This academic article, utilizing an analytical literature review, aimed to explore the multifaceted roles of English for Specific Purposes (ESP) practitioners. It was found that there were five key roles responsible by the practitioners: (1) teaching; (2) course designing and material providing; (3) researching; (4) collaborating; and (5) evaluating. Performing the teaching role, practitioners facilitate learning, integrate subject-specific content, and foster authentic communication. As course designers and material providers, ESP practitioners adopt language-centered, skills-centered, and learning-centered approaches, as well as the cyclical process of needs analysis, ensuring relevance and authenticity in their courses. ESP practitioners, in their role as researchers, actively participate in action research to develop their professional identities within the ESP context. Collaboration with subject teachers and colleagues also emerges as a crucial aspect, ranging from cooperation to team-teaching, with associated challenges. Lastly, ESP practitioners serve as evaluators, assessing teaching methods, materials, and student learning outcomes, emphasizing fair and constructive evaluation aligned with academic and professional achievements. The discussion highlights the dynamic and comprehensive nature of ESP practitioners’ responsibilities, requiring ongoing adaptation and improvement in response to the evolving demands of ESP instruction. Moreover, clear national educational and language policies of English as a Foreign Language (EFL) countries should be emphasized to succeed in their ESP education.